Peningkatan Kapasitas Pelaku UMKM di Desa Sei Rampah dalam Mengoptimalkan Media Sosial di Era Pemasaran Digital - Rodi Syafrizal; Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Suci Etri Jayanti S; Daniel Collyn; Yenni Mariani Sinurat; Ayu Zurlaini Damanik; Suwadi Suwadi; Yomeini M. Sagala; Murbanto Sinaga; Sri Winda Hardiyanti Damanik (Universitas Kristen Indonesia Toraja, 2025)
The understanding of most MSME (Micro, Small, and Medium Enterprise) actors in Sei Rampah Village regarding the workings and utilization of social media as a digital marketing platform remains relatively low. This condition prompted the community service team to conduct a community engagement activity in the village. The activity was designed in the form of socialization and interactive training aimed at helping MSME actors comprehend how to optimally leverage social media to increase sales and expand market reach. The socialization activity was attended by 20 participants. The methods used in this community service activity were lectures and interactive discussions. The stages of the activity included the preparation phase and the implementation phase. This activity had a positive impact by assisting business actors in understanding how to optimally utilize social media to boost sales and broaden their market reach. Following the socialization, the majority of participants expressed interest in using social media as a platform for marketing their products. This indicates that the community engagement activity carried out contributed positively to business actors in Sei Rampah Village.